Hypericum hircinum L.: Botany, Traditional Uses, Phytochemistry, and Pharmacological Properties - Noemi Tocci; Manuel Pramsohler; Lorenza Conterno; Tobias Weil (Plants)
Hypericum hircinum L., commonly known as goat St. John’s wort or stinking tutsan, is a medicinal plant native to the Mediterranean basin and widespread across Europe and parts of the Middle East. It has a long history of traditional uses in folk medicine to treat respiratory diseases, wounds, and burns and to relieve migraine, rheumatism, and muscular pains. Despite numerous scientific studies shading light on the phytochemical profile and on the beneficial properties of the plant extracts, a comprehensive overview of the current knowledge is missing. In this paper, we summarized the available information on botany, traditional uses, phytochemistry, and pharmacological properties of Hypericum hircinum from peer-reviewed articles published till March 2025 in PubMed, ScienceDirect, Wiley, Springer, ACS, Scielo, and Web of Science databases. The presence of numerous valuable compounds, including terpenes, phenolic acids, flavonoids, and phloroglucinols, is reported as well as the wide range of pharmacological properties, such as antimicrobial, antifungal, antiviral, antidepressant, anti-collagenase, anti-α-glucosidase, and antioxidant activities, together with non-pharmacological properties. The data reported in this review contribute to a deeper understanding of the biological properties of the species and pave the way for further investigation of its potential applications.